Mystical perspectives in interreligious dialogue - Waaijman, K. (Acta Theologica, 2008)
This article discusses the distinction that is being made between the unknowability of God, the source of all that is, and Jesus of Nazareth, the body language of God, from the viewpoint of spirituality with Paul’s address at the Areopagus in Athens (Acts 17:16-32) as point of departure. This speech virtually represents the oldest Christian interfaith meeting in which there is a dialogue between religious Athenians and Paul. The article reflects, first of all, on Paul’s reaction to the questions and challenges of the Epicurean and Stoic philosophers in his audience that relates to this distinction. A second part will investigate the mystical unity of the unknowable God and his body language in Christ. In a third part some mystical perspectives on this distinction in Islam will be analysed.